DEVELOPMENT PHYSICS WORKSHEET INTEGRATED SCIENTIFIC LITERACY USING A CONSTRUCTIVE APPROACH ON PARABOLIC MOTION MATERIALS - Fatimah Zahara; Renol Afrizon (PILLAR OF PHYSICS EDUCATION, 2023)
The 2013 curriculum requires teachers to be skilled in the process of learning which makes students more active in learning activities. The solution to overcome this problem is to develop physics worksheets with scientific literacy using a constructivist approach. This study aims to produce worksheets filled with scientific literacy using a constructivist approach to parabolic motion for class X high school that is valid and practical. This research is a Research and Development research type using the Plomp development model. The development process in this study is limited to one-to-one practicality which ada at the development stage which functions to see the practicality of the product being made. Validation was carried out by 3 physics lecturers from UNP Faculty of Mathematics and Natural Sciences and practicality was carried out by teachers and students senior high school. The data collection instruments in this study are validity and practicality sheets. The data analysis technique for product validation uses the Aiken's V index. Based on data analysis from the research that has been done, it can be determined the results of the study, namely the validity results of the worksheet with score in average of 0.92 in the category in medium and practicality with an average of 89.7%. . So, it can be concluded that physics worksheets with scientific literacy using a constructivist approach to parabolic motion are appropriate for use by teachers and students in the process of learning..